The restoration of the textile tabernacle of the Venerable Confraternity of Our Lady of Lampedusa: looking into the sacred - Vígio, Thainá (2025)
Tabernacles are the heart of the main altar of a church and must be in good condition to fulfill the sacred function of the Eucharist. In Rio de Janeiro, in the Centro neighborhood, at the Venerable Confraternity of Our Lady of Lampedusa, located in the Lampedusa Church, there is a rare surviving example of a sacrarium made of textile structure. It consists of damask linings with golden metallic trimmings, fringes, cotton, and synthetic fabrics. Interventions on active religious objects need to be in constant dialogue between the needs of worship and the conservators’ ethics. In this sense, museum conservation was the methodology used, respecting the temporal marks and minimal intervention. This article presents the processes of material identification, condition report, and restoration of our precious heritage, which may once again shine brightly.